Trend of Changing Morphological Pattern of Adult Nephrotic Syndrome, Global and Bangladesh Perspective (Journal of Armed Forces Medical College, Bangladesh, 2016)
Nephrotic Syndrome (NS) is a clinical condition characterized by massive proteinuria, hypoalbuminemia, hypercholesterolemia, and generalized oedema. It occurs more commonly in children than in adults, and usually manifests as one of two usually idiopathic diseases: Minimal change NS (MCNS) or focal segmental glomerulosclerosis (FSGS). It has also an incidence of three new cases per 100000 each year in adults. During 70s and 80s membranous nephropathy was considered to be the prime cause of adult NS worldwide. In USA, Brazil, Singapore and South East Asian countries specially in India and Pakistan FSGS has exceeded all other causes of adult NS during last three decades. While in most of the countries of Europe, Australia, Japan, Iran IgA nephropathy has become the main cause of adult NS. Membranoproliferative glomerulonephritis (MPGN) is the predominant cause in certain countries like Russia, South Africa, Singapore etc. In some countries like UAE and Nepal MN is still found to be the main cause of adult NS. In Bangladesh only a few studies are documented which show variable predominant causes of adult NS. It is possibly due to inconsistent renal pathology facilities available in the countries and lack of dedicated renal pathologists.Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 100-108